2021
DOI: 10.1186/s43897-021-00015-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of postharvest flower opening and senescence

Abstract: Flowers are key organs in many ornamental plants, and various phases of flower development impact their economic value. The final stage of petal development is associated with flower senescence, which is an irreversible process involving programmed cell death, and premature senescence of cut flowers often results in major losses in quality during postharvest handling. Flower opening and senescence are two sequential processes. As flowers open, the stamens are exposed to attract pollinators. Once pollination oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 122 publications
1
17
0
Order By: Relevance
“…Based on our previous results, we de ned stage 0 as " oral bud revealed" and stage 2 as "sepal completely unfold." Microscopy observations indicated that division of petal cells almost stops at stage 2, while cell expansion drove petal growth from stage 2 onward [29][30][31] The above dataset revealed that the abundance of microRNA159 (miR159) exhibits a sharp drop in petals from cell division (stage 0) to cell expansion (5 days after stage 0) (Fig. 1A) 19,30,32 .…”
Section: Results Mir159 Controls Cell Expansion and Ower Opening By T...mentioning
confidence: 91%
See 1 more Smart Citation
“…Based on our previous results, we de ned stage 0 as " oral bud revealed" and stage 2 as "sepal completely unfold." Microscopy observations indicated that division of petal cells almost stops at stage 2, while cell expansion drove petal growth from stage 2 onward [29][30][31] The above dataset revealed that the abundance of microRNA159 (miR159) exhibits a sharp drop in petals from cell division (stage 0) to cell expansion (5 days after stage 0) (Fig. 1A) 19,30,32 .…”
Section: Results Mir159 Controls Cell Expansion and Ower Opening By T...mentioning
confidence: 91%
“…Organ growth requires coordination between cell division and cell expansion 27,28 . In petals, cell division mostly ceases before anthesis, and ower opening is largely attributed to cell expansion [29][30][31] . To understand the underlying mechanism of the transition between cell division and cell expansion, we previously conducted a transcriptome deep sequencing (RNA-seq) analysis of short RNAs and transcripts from petals to investigate gene expression pro les during the cell division and expansion phases.…”
Section: Results Mir159 Controls Cell Expansion and Ower Opening By T...mentioning
confidence: 99%
“…Two research articles in the collection report the most recent findings that AtNAP promotes leaf senescence by activating the gene of cytokinin oxidase 3 (that degrades senescence-inhibiting plant hormone cytokinins) (Hu et al 2021) Flowers are "food for the mind, ' and senescence of flowers limits vase life and reduces aesthetic appreciation. In this special collection there are one review article (Sun et al 2021) and one research article (Zou et al 2021) representing the frontiers in flower senescence research. Many flowers, especially cut flowers such as rose, undergo opening and senescence processes after harvest.…”
mentioning
confidence: 99%
“…Larger flowers are valuable in terms of both evolution and the economy. Changes to internal and external cues of the flower opening process can be responsible for alterations in the flower size [ 1 ]. However, the regulatory mechanism of flower opening is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Cell expansion, a vital factor that shapes the morphology of plant organs and enables their optimal growth in response to environmental cues [ 6 ], depends largely on a coordination of cell wall metabolism, cell turgor, and cytoskeletal reorganization [ 7 ]. Ethylene can promote flower opening in many ornamental plants [ 1 ]. In rose, ethylene accelerates flower opening while inhibiting petal expansion [ 5 , 8 , 9 ], and its regulation of flower opening is through the upregulation of gene-encoding ethylene receptors [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%